Mathematical-procedural Knowledge ant its relation to logical-mathematical intelligence among students at the third stage in mathematics department (Journal Of Educational and Psychological Researches, 2018)
The study seeks the relationship between the mathematical-procedural Knowledge and the logical-mathematical intelligence among students at the third stage in mathematics department. To this end, three questions were arisen: what is the level of mathematical-procedural Knowledge among the third stage students in mathematics department regarding their gender? Do male or female students have more logical-mathematical intelligence and are there significant differences base on their gender? What kind of correlation is between the level of mathematical-procedural Knowledge and the logical-mathematical intelligence of male and female students in the third stage in the mathematics department? A sample of (75) male and female students at the third stage in mathematics department were selected from college of education for pure sciences \ University of Baghdad. The researcher has developed two scales: one to measure the mathematical-procedural Knowledge consisted of (8) items, and the other to measure logical-mathematical intelligence composed of (10) items. The findings revealed a correlation relationship between the mathematical-procedural Knowledge and the logical-mathematical intelligence foe sample as a whole. It also found students have logical-mathematical intelligence comparing to the mathematical-procedural Knowledge that showed a low level.